Influenza vaccine coverage and predictors of vaccination among aged care workers in Sydney Australia. Issue 8 (18th February 2020) - Lai, Elisa; Tan, Hao Yi; Kunasekaran, Mohana; Chughtai, Abrar Ahmad; Trent, Mallory; Poulos, Christopher; MacIntyre, C. Raina
Highlights: Current influenza vaccination uptake amongst Australian ACWs remain suboptimal at 48%. The aged care workforce has a large proportion of migrant workers. Optimising workplace vaccination policies can greatly increase vaccine coverage. Onsite provision of vaccines overcomes many deterrents to vaccination amongst AWCs. Abstract: Aged care facilities (ACFs) are residential communities with a concentration of vulnerable individuals with increased risk of severe influenza infection and complications such as outbreaks, hospitalisations and deaths. Aged care workers (ACW) are potential sources of influenza introduction and transmission in ACFs. Little is known about vaccine uptake among ACW. This study aimed to measure the vaccine uptake rate among Australian ACW and evaluate the demographic determinants of uptake during the influenza season of 2018. 146 ACWs were recruited from 7 facilities of a multisite aged care provider in Sydney. ACWs completed a questionnaire regarding their demographic, occupational and vaccination status. Vaccine coverage was calculated and variables were examined against their 2018 influenza vaccination status in statistical analysis. ACWs in our study were predominantly from a non-health occupational background with a large proportion of migrant workers (56%, 75/134). Vaccine coverage in 2018 was 48% (65/135). The strongest determinants of vaccine uptake were previous year vaccination history (Odds Ratio [OR] 10.49, 95% CI 3.33–33.10), workplace immunisation programs for employees (OR 7.87, 95% CI 2.47–25.10), casual work as employment status (OR 0.14, 95% CI 0.02–0.77), and presence of comorbidities (OR 4.04, 95% CI 1.23–13.32). ACW are a unique and understudied group who are critical to infection control in ACFs. Few ACWs have formal health training, and many are migrants who may lack access to subsidised health care and face out of pocket costs for vaccination. Vaccine coverage among ACW were below recommended levels. Provision of influenza vaccine for staff in workplaces is highly effective in raising vaccine coverage amongst ACWs. More research on the aged care sector workforce is needed in order to evaluate the determinants of vaccine uptake among Australian ACWs.